Zbtb46 expression distinguishes classical dendritic cells and their committed progenitors from other immune lineages - Satpathy, Ansuman T. (The Rockefeller University Press, 2012)
Distinguishing dendritic cells (DCs) from other cells of the mononuclear phagocyte system is complicated by the shared expression of cell surface markers such as CD11c. In this study, we identified Zbtb46 (BTBD4) as a transcription factor selectively expressed by classical DCs (cDCs) and their committed progenitors but not by plasmacytoid DCs (pDCs), monocytes, macrophages, or other lymphoid or myeloid lineages. Using homologous recombination, we replaced the first coding exon of Zbtb46 with GFP to inactivate the locus while allowing detection of Zbtb46 expression. GFP expression in Zbtb46(gfp/+) mice recapitulated the cDC-specific expression of the native locus, being restricted to cDC precursors (pre-cDCs) and lymphoid organ– and tissue-resident cDCs. GFP(+) pre-cDCs had restricted developmental potential, generating cDCs but not pDCs, monocytes, or macrophages. Outside the immune system, Zbtb46 was expressed in committed erythroid progenitors and endothelial cell populations. Zbtb46 overexpression in bone marrow progenitor cells inhibited granulocyte potential and promoted cDC development, and although cDCs developed in Zbtb46(gfp/gfp) (Zbtb46 deficient) mice, they maintained expression of granulocyte colony-stimulating factor and leukemia inhibitory factor receptors, which are normally down-regulated in cDCs. Thus, Zbtb46 may help enforce cDC identity by restricting responsiveness to non-DC growth factors and may serve as a useful marker to identify rare cDC progenitors and distinguish between cDCs and other mononuclear phagocyte lineages.